Womenas Empowerment : Concept and Beyond (Global Journal of Human-Social Science, 2013)
Long before the word `empowerment' became popular, women were speaking about gaining control over their lives, and participating in making the decisions that affect them in home and community, in government and international development policies. But problem is, very few have clear conception on empowerment. This is very easy to say but difficult to understand what is empowerment? This article takes an initiative to clarify the concept based on several scholar's views. And finally, make a conclusion with alternative analysis of women's empowerment.
Keywords: empowerment; women; power; gender; selfreliance; decision-making control over